PENERAPAN KONSEP GUGUS KENDALI MUTU UNTUK MENGURANGI WAKTU PRODUKSI PADA USAHA PEMBUATAN ROTI (STUDI KASUS PADA UMKM JAKARTA SELATAN) - Meilan Agustin (Fakultas Teknik Universitas Borobudur, 2019)
Roti Mungil ABS is a Micro and Medium Small Business that has a bread making business. As the journey of Roti Mungil ABC business is growing rapidly, but unfortunately not balanced by adequate production capability. Improvements are made only to the addition of manpower, not process improvement. The use of the Quality Control (GKM) method allows the active role of workers to contribute their ideas and suggestions to the company's progress. In this study, preliminary findings illustrate that about 33% of the time spent on bread making, is in the proofing process. With details of the time required to make a dough is 225 minutes, of which 75 minutes are spent on the proofing process. By using the Fishbone Diagram seen proofing process is still done simply, so the suggestions that arise is how to create a tool that can help accelerate the proofing process. After passing eight steps to improve the GKM, the result of repairing the proofing process time to 45 minutes, so the total time required for one dough to 195 minutesKey Words: Gugus Kendali Mutu, Seven Tools, Continous Impprovement.